Modernización, implantación de sistemas de ayudas visuales luminosas para la navegación aérea en el Aeropuerto Internacional Cotopaxi - Anchatipán Navas, Luis Arturo (2015)
This research was carried out at “Cotopaxi International Airport”, where the importance of aerial navigation is determinated to guide the pilot securely and effectively during landing off and parking, for this reason, it has been put into research and project implementation: "VISUAL AIDS UPDATING AND IMPLEMENTATION FOR AERIAL NAVIGATION AT COTOPAXI INTERNATIONAL AIRPORT".A field investigation, bibliographic/documentary and descriptive methodology were applied in this research, linked with some techniques for gathering information such as: survey and interview. The principal actors are the pilots and aeronautical personnel (DGAC) from different areas involved in aeronautical operations. It is important to improve and update visual aids systems for aerial navigation, using leading technology, implementing LED lighting type, contributing to energy saving, preserving natural resources and protecting the environment. Based on corrective and preventive maintenance experience, it has been necessary to mention a summary about the main tasks of systems and equipment inspection, to help reducing MTBF and MTBO, with the result to close the airport totally or partially.